Radiative magneto-micropolar fluid flow over a stretching/shrinking sheet with slip flow model - Kamran, M.; Wiwatanapataphee, Benchawan (2018)
© Published under licence by IOP Publishing Ltd. This paper presents a study of mixed convective magneto-micropolar fluid flow over a porous stretching/shrinking surface under slip boundary condition in the presence of the thermal radiation effect. The impact of the Newtonian heating is assumed in the thermal boundary condition. The proposed governing flow model is transformed and solved by a semi-analytical technique named Homotopy Analysis Method, and the obtained solutions have excellent agreements with the analytical and the numerical results under special cases. The obtained results reveal that when the sheet stretches at a higher magnetic field parameter, the velocity boundary layer thickness becomes shorter with an increase in the thermal radiation parameter as compared to the lower value of the magnetic field parameter. On the other hand, a higher value of the thermal radiation parameter causes to produce a wider thermal boundary layer thickness as the value of the magnetic field parameter enhances. However, at a lower value of the thermal radiation parameter yields a significant change in the temperature of the micropolar fluid flow. MHD radiative micropolar fluid flow may have an important consideration in magnetic resonance imaging (MRI) and in the circulatory system to control the blood flow by considering the slip flow regime.